Commissioning a High‐Recovery Brackish Groundwater Desalination Plant in San Antonio. Issue 7 (1st July 2019) - Shirazi, Saqib H.; Hernandez, Andrew J.; Morrison, Kevin
Abstract : Optimizing San Antonio Water System's new desalination plant yielded operational strategies and lessons learned for engineers and operators.